Barriers to the Broad Dissemination of Creative Works in the Arab World - Schwartz, Lowell H. (RAND Corporation, 2009)
A growing body of creative works by Arab authors and artists counters the intellectual and ideological underpinnings of violent extremism. Unfortunately, many of these works are not widely disseminated, marginalizing the influence of these alternative voices. This monograph examines the barriers to the broad dissemination of such works, with a focus on Arabic literature, and suggests ways to overcome these barriers.